Independent women: from film to television. Issue 7 (3rd October 2019) - Perkins, Claire; Schreiber, Michele
ABSTRACT: "Independent Women: From Film to Television" explores the significance for feminism of the increasing representation of women on and behind the screen in television contexts around the world. "Independent" has functioned throughout film and television history as an important euphemism for "feminist, " and this special issue investigates how this connection plays out in a contemporary environment that popular feminist discourse is constructing as a golden age of television for women. The original essays offer keen insight into how post-network television is being valued as a new site of independent production for women, and examine how the connotations of creative control that attend this orients perceptions of both female creators and their content as feminist. Together, they provide a compelling perspective on the feminist consequences of how independence and "indie" have intensified as cultural sensibilities that coincide and engage with the digital transformation of television over the past decade.